Study on the influences of oil supply pressure and maximum opening of electromagnetic valve on upstream pressure fluctuation. (March 2021) - Han, Zhiqiang; Hu, Mingyan; Zhao, Jiahui; Yu, Wenbin
The pressure fluctuation in the hydraulic pipeline in the electro-hydraulic variable valve mechanism will cause the instability of the oil pressure in the hydraulic chamber, thereby making the valve movement characteristics unpredictable, which can affect the adjustment function of the valve mechanism to the air intake, and further affect the combustion, emission, and fuel consumption of the engine. In this article, a simulation model is established for the working process of a certain type of marine diesel engine's electro-hydraulic variable valve system, and the simulation and experiment are combined to study the influence of the hydraulic oil supply pressure P 0 (10–13 MPa) and the maximum opening d (2.5–4 mm) of the electromagnetic valve on the upstream instantaneous pressure variation of the hydraulic circuit of the electromagnetic valve. The fluctuation curve of instantaneous pressure variation is divided into three stages (I a–b, II b–c–d, and III d–e ), and the characteristic values ( Pa, Pb, Pc, Pd, Pe ) and characteristic phases ( βa, βb, βc, βd, βe ) at the inflection point of the fluctuation curve are selected to describe the influence of the hydraulic oil supply pressure and the maximum opening of the inlet electromagnetic valve on the upstream instantaneous pressure variation of the hydraulic circuit of the electromagnetic valve. The result shows that the decrease in the characteristic parameters Pa and Pc values and the increase in the Pb and Pd values increase with the increase in the oil supply pressure and the maximum opening. When the maximum opening is constant, the decrease in the characteristic parameter Pe value increases with the increase in the oil supply pressure; when the oil supply pressure remains unchanged, the difference in the characteristic parameter Pe value is less than 0.04 MPa at different maximum openings, which is hardly affected by the maximum opening; and the influence of the oil supply pressure and the maximum opening on the characteristic phase βa-e is very different.